PENGUKURAN TINGKAT RISIKO DAN KEUNTUNGAN SAHAM INDIVIDUAL DENGAN MENGGUNAKAN PENDEKATAN HISTORIS PADA METODE VALUE AT RISK (VaR) (STUDI KASUS TOP 10 SAHAM TERBAIK JANUARI 2022) - Perli Iswanto; Aditya Rian Ramadhan (Jurnal Akuntansi dan Manajemen Bisnis, 2022)
In research has been conducted to measure individual daily in January 2022 which is included in the Top 10 best stocks version of kontan.co.id risk and profit level using the Value at Risk (VaR) approach. The research method used to analyze the data refers to the Historical Simulation Model approach. The data used is the daily asset return data obtained from the daily closing price of shares during the January 2021 period. The results of the VaR method approach are Historical Simulation. The model shows CMPP stock with a risk of 91 million. The measurement results show that if the funds invested are Rp. 500,000,000.00 with a 95% confidence level, the period is 21 days.